Achillea millefolium L. as a Recommendation for the Management of Hysteria - Somaye Zakeri (Tehran University of Medical Sciences, 2020)
Hysteria is an intricate disorder which the exact reason has not yet been determined. Sensory-motor symptoms such as falling down, aphonia and jerky movements are common and similar to seizure-like disorders, except that the patient remembers everything after waking up. Non-organic reasons are the most prominent explanations for this situation. Many treatments are offered for hysteria but patients still wander between psychiatrists and neurologists and suffer therapeutic failures, relapses and burden of disease. Persian medicine as an old medical school has clear definitions about the physiopathology and experienced therapeutic suggestions for hysteria. Since this situation can influence patient quality of life, it is worthwhile to find a solution for this debilitative disorder.